Zinc-air battery integrated negative electrode and preparation method and application thereof

The negative electrode of zinc air battery was prepared by using metal consolidation method of composite zinc powder and three-dimensional continuous carbon network structure, and the problems of zinc negative electrode deposition unevenness and insufficient mechanical strength were solved, and the cycle life and discharge capacity of the battery were significantly improved.

CN119517944AActive Publication Date: 2025-02-25ZIBO TORCH ENERGY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510091704.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In practical applications, the zinc negative electrode of zinc air batteries faces the problems of zinc ion deposition inconsistent leading to the decline in dendrites' growth, safety and cycle life.

Method used

Composite zinc powder is used as the negative electrode raw material, and the composite zinc powder precursor is obtained by ball milling and vacuum drying. Then, in-situ pyrolysis is carried out under a hydrogen-argon mixed gas environment to form a spherical composite zinc powder, and it is made into a block negative electrode by metal consolidation method, with a built-in three-dimensional continuous carbon network structure.

Benefits of technology

The mechanical strength of the zinc negative electrode is improved, dendrites are inhibited, the cycle life and discharge capacity of the battery are improved, and the utilization rate of the active substances of the negative electrode is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517944A_ABST
    Figure CN119517944A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrodes and preparation thereof, and particularly relates to a zinc-air battery integrated negative electrode and a preparation method and application thereof. The preparation method of the integrated negative electrode of the zinc-air battery comprises the following steps: adding a carbon source material and zinc powder into a solvent, carrying out ball-milling mixing, and drying, grinding and sieving under a vacuum condition to obtain a composite zinc powder precursor; performing in-situ pyrolysis on the composite zinc powder precursor in a hydrogen-argon mixed gas environment to obtain composite zinc powder; and mixing the composite zinc powder with a solubilizer, carrying out ultrasonic treatment, and preparing a blocky negative electrode by using a metal consolidation method to obtain the zinc-air battery integrated negative electrode. The preparation method of the integrated negative electrode of the zinc-air battery, provided by the invention, is simple to operate and stable in process. The zinc-air battery integrated negative electrode prepared by the invention is compact in internal structure. The zinc-air battery integrated negative electrode prepared by the method is applied to preparation of a zinc-air battery, and is high in discharge capacity, high in rate capability and long in cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrodes and preparation thereof, and specifically relates to an integrated negative electrode for a zinc-air battery and a preparation method and application thereof. Background Art

[0002] Zinc-air batteries have the characteristics of low cost, high safety, high energy density and environmental friendliness, and have become the key batteries in the field of energy storage power sources. However, zinc, the negative electrode material of zinc-air batteries, faces a series of challenges in practical applications. The primary problem lies in the unevenness of zinc ions during the deposition process, which leads to the growth of dendrites. Dendrites may not only pierce the battery separator and cause internal short circuits, but also reduce the safety and cycle life of the battery. In addition, metallic zinc is prone to hydrogen evolution side reactions and electrochemical corrosion in an alkaline electrolyte environment. These problems together lead to a significant decrease in the reversibility and utilization of the zinc negative electrode.

[0003] It has been modified in the prior art. These modifications are mainly concentrated on the surface of zinc foil or the interface between zinc negative electrode and electrolyte, aiming to reduce the polarization potential of reversible deposition of zinc ions by optimizing the interface properties, thereby improving the stability of the battery. Although these efforts have achieved certain results, the zinc negative electrode still faces bottleneck problems such as low utilization rate, poor long-term cycle performance, high cost and complex preparation process.

[0004] To solve the above problems, the improvement is to use zinc powder as the negative electrode raw material. Compared with zinc foil, zinc powder has better processability and is easy to be compounded with binders, conductive agents and other materials to prepare zinc paste negative electrodes. However, the current preparation methods of zinc paste negative electrodes, such as die casting or coating methods, result in loose negative electrode materials with insufficient mechanical strength, which is difficult to meet the requirements of long-term battery cycles.

[0005] CN117613185A discloses a method for preparing a zinc negative electrode for a zinc-air battery, comprising the following steps: firstly, mixing zinc powder and zinc oxide powder, adding fiber and conductive agent, continuing to stir, and then adding a binder to prepare a zinc paste; then applying and pressing the prepared zinc paste onto a galvanized copper mesh to obtain a negative electrode grid; and finally curing the negative electrode grid to obtain a zinc negative electrode for a zinc-air battery. This method is a paste-coated negative electrode, and the prepared negative electrode has a loose structure and no mechanical strength. During the charge and discharge cycle, the negative electrode is very likely to have problems such as expansion deformation and active material shedding, thereby affecting the discharge capacity and cycle life of the battery. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, and provide a method for preparing an integrated negative electrode of a zinc-air battery, which is simple to operate, has a stable process, and has feasible scale potential. The integrated negative electrode of the zinc-air battery prepared by the present invention has a compact internal structure and a prolonged service life. The integrated negative electrode of the zinc-air battery prepared by the present invention is applied to prepare a zinc-air battery, which has a high discharge capacity, a strong rate performance, and a long cycle life.

[0007] The method for preparing the integrated negative electrode of the zinc-air battery of the present invention comprises the following steps: (1) Preparation of composite zinc powder precursor: adding carbon source material and zinc powder into deionized water, mixing by ball milling, drying under vacuum conditions, grinding and sieving to obtain composite zinc powder precursor; (2) Preparation of composite zinc powder: The composite zinc powder precursor is pyrolyzed in situ in a hydrogen-argon mixed gas environment to obtain composite zinc powder; (3) Negative electrode preparation: The composite zinc powder is mixed with a solubilizer, and after ultrasonic treatment, a block negative electrode is prepared by a metal consolidation method to obtain an integrated negative electrode for a zinc-air battery.

[0008] The mass ratio of the carbon source material to the zinc powder in step (1) is 1:1-15.

[0009] The carbon source material in step (1) is one of glucose, sucrose, lactose, starch and cellulose.

[0010] The ball milling mixing time of step (1) is 2-8 hours, the drying temperature under vacuum conditions is -10-5°C, the drying time under vacuum conditions is 24-48 hours, and the average particle size of the composite zinc powder precursor after grinding and sieving is 5-10 μm.

[0011] The temperature of the in-situ pyrolysis in step (2) is 650-850°C, and the time of the in-situ pyrolysis is 2-7h.

[0012] The solubilizer in step (3) is one or more of cyclodextrin, nano calcium oxide particles, potassium acetate, urea, acetamide, and nicotinamide, and the particle size of the solubilizer is ≤50 nm.

[0013] The amount of the solubilizing agent used in step (3) is 0.1-5% of the mass of the spherical composite zinc powder.

[0014] The metal consolidation method in step (3) is one of spark plasma sintering, 3D printing, cold pressing and compression molding.

[0015] A zinc-air battery integrated negative electrode is prepared by the preparation method of the zinc-air battery integrated negative electrode.

[0016] Application of the zinc-air battery integrated negative electrode: after the prepared zinc-air battery integrated negative electrode is made into a negative electrode according to size and shape, it is assembled into an air battery with an air positive electrode and an alkaline electrolyte.

[0017] The air positive electrode is a positive electrode with a sandwich structure, including a gas diffusion layer, a catalyst layer and a carbon cloth current collector, and the positive electrode is a commercially available product.

[0018] The alkaline electrolyte is a mixed solution of 6M KOH and 2% zinc acetate.

[0019] Specifically, the method for preparing the integrated negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: Add carbon source material and zinc powder in a mass ratio of 1:1-15 into deionized water, fully mix and stir in a planetary ball mill for 2-8 hours, dry at -10-5°C under vacuum for 24-48 hours, grind and sieve to obtain a composite zinc powder precursor with an average particle size of 5-10 μm; (2) Preparation of composite zinc powder: The composite zinc powder precursor is pyrolyzed at 650°C-850°C in a hydrogen-argon mixed gas environment for 2-7 hours, and the carbon source material uniformly wrapped on the surface of the Zn powder is in situ pyrolyzed into a carbon layer to obtain a composite zinc powder with a good loosely stacked spherical structure. The average particle size is measured to be 5-12 μm; (3) Negative electrode preparation: The spherical composite zinc powder was mixed with 0.1-5% of a solubilizer, and then ultrasonically treated for 30 min to prepare a block negative electrode using a metal consolidation method to obtain an integrated negative electrode for a zinc-air battery.

[0020] The present invention utilizes a metal consolidation method to rapidly sinter the composite zinc powder wrapped in a carbon layer at a low temperature to obtain a pole piece with high mechanical strength, thereby avoiding the loose structure of the zinc powder anode and the low conductivity caused by the use of a binder in the past, and improving the overall performance of the electrode.

[0021] The key to the present invention is to generate a carbon layer in situ on the surface of zinc powder, and connect it to form a three-dimensional carbon network structure dispersedly distributed inside the bulk phase. The three-dimensional carbon network structure provides more nucleation sites for zinc ions, which is conducive to the uniform deposition of zinc, inhibits the formation of dendrites, and realizes the overall regulation of the reversible deposition of zinc from the bulk phase; at the same time, the three-dimensional continuous carbon network structure can be used as an electron transmission channel between zinc powders, avoiding the increase in resistance caused by point contact between zinc powders, improving the conductivity of the electrode, and is conducive to the deep charging and discharging of the battery, and improving the utilization rate of the active material of the negative electrode. In the present invention, small particles (≤50nm) of solubilizer are added to the large particles of composite zinc powder (particle size is 5-12μm), and the solubilizer is uniformly distributed inside the zinc negative electrode. As the reaction continues, the solubilizer is gradually released and dissolved in the electrolyte, which can effectively increase the solubility of zincate in the electrolyte, greatly reduce the decomposition and deposition of zinc oxide at the negative electrode or positive electrode, and then inhibit the growth of zinc dendrites and deformation of the negative electrode, thereby significantly improving the cycle life of the zinc-air battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention provides a new design perspective for the regulation of zinc metal anodes, and can also be extended to the preparation and bulk phase regulation of other metal anodes, with strong universality. The mature use of metal consolidation method and the practicality of zinc powder make this preparation method have the potential for large-scale application.

[0023] (2) The negative electrode prepared by the present invention has a compact internal structure and a built-in three-dimensional continuous carbon network structure that can serve as a continuous electron transmission channel between zinc powders, thereby improving the utilization rate of the active material of the negative electrode. At the same time, the incorporation of a solubilizer increases the solubility of zincate in the electrolyte, which can effectively increase the solubility of zincate in the electrolyte, inhibit zinc dendrite growth and negative electrode deformation, and significantly improve the cycle life of the battery.

[0024] (3) The present invention is applied to the manufacture of air batteries, which increases the discharge capacity of the negative electrode and improves the electrochemical reversibility of the zinc negative electrode, thereby greatly improving the discharge capacity, rate performance and cycle life of the battery, and accelerating the promotion and application of zinc-air battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the results of ohmic impedance testing of batteries prepared in Examples 1-5 and Comparative Examples 1-3.

[0026] Figure 2 Schematic diagram of the results of constant current charge and discharge tests on the batteries prepared in Examples 1-4 and Comparative Examples 1-3.

[0027] Figure 3 Schematic diagram of the results of LSV performance testing of batteries prepared in Examples 1-4 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments.

[0029] The raw materials and auxiliary agents used in the following examples are all commercially available products. The particle size of the solubilizer used is ≤50nm.

[0030] The purchased positive electrode is a normal commercially available rechargeable air electrode, model C20 168×(218+8) mm, open circuit voltage 1.35-1.5 volts, circuit density 50 mA / cm 2 , cycle life is 10mA / cm 2 It can be charged and discharged for more than 500 hours and is commercially available at Hunan Yuanda New Materials Co., Ltd.

[0031] Example 1 The preparation method of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: Glucose and zinc powder were weighed in a mass ratio of 1:6, and then added into deionized water. The mixture was thoroughly mixed and stirred in a planetary ball mill for 4 h at a stirring temperature of ≤40 °C. After the mixing was completed, the precursor powder was moved to a vacuum high and low temperature oven for drying at 0 °C for 30 h. The precursor powder was ground and sieved to obtain a composite zinc powder precursor with an average particle size of 8 μm.

[0032] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed in a hydrogen-argon mixed gas environment at 650°C for 7 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 5 μm.

[0033] (3) Negative electrode preparation: The spherical composite zinc powder was mixed with 2% urea, and after ultrasonic treatment for 30 min, the mixed powder was solidified into a block negative electrode by spark plasma sintering at a temperature of 360 °C and a pressure of 500 MPa to obtain an integrated negative electrode for zinc-air batteries.

[0034] (4) Preparation of zinc-air battery: The integrated negative electrode of the zinc-air battery is cut into a size of 40 mm × 40 mm × 5 mm, and then prepared into a negative electrode by welding the electrode ears, and assembled with the purchased positive electrode into a battery for standby use, which is numbered 1#.

[0035] Example 2 The preparation method of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: Weigh starch and zinc powder in a mass ratio of 1:15, then add them into deionized water, and mix them thoroughly in a planetary ball mill for 8 h at a stirring temperature of ≤40 °C. After stirring, move the precursor powder to a vacuum high and low temperature oven for drying at -10 °C for 24 h, grind and sieve to obtain a composite zinc powder precursor with an average particle size of 5-10 μm.

[0036] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed at 700°C in a hydrogen-argon mixed gas environment for 5 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 7 μm.

[0037] (3) Negative electrode preparation: The spherical composite zinc powder was mixed with 0.1% nano-calcium oxide particles, and after ultrasonic treatment for 30 min, the mixed powder was printed into a block negative electrode using a 3D printing method to obtain an integrated negative electrode for a zinc-air battery.

[0038] (4) Preparation of zinc-air battery: The integrated negative electrode of the zinc-air battery is cut into a size of 40 mm × 40 mm × 5 mm, and then prepared into a negative electrode by welding the electrode ears, and assembled with the purchased positive electrode into a battery for standby use, which is numbered 2#.

[0039] Example 3 The preparation method of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: First weigh sucrose and zinc powder in a mass ratio of 1:1, then add them into deionized water, and mix them thoroughly in a planetary ball mill for 2 h at a stirring temperature of ≤40 °C. After stirring, move the precursor powder to a vacuum high and low temperature oven for drying at 5 °C for 48 h, grind and sieve to obtain a composite zinc powder precursor with an average particle size of 5-10 μm.

[0040] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed in a hydrogen-argon mixed gas environment at 850°C for 2 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 10 μm.

[0041] (3) Negative electrode preparation: The spherical composite zinc powder was mixed with 5% acetamide, and after ultrasonic treatment for 30 min, the mixed powder was pressed into a block negative electrode by cold pressing sintering method at a temperature of ≤50 °C and a pressure of 200 MPa to obtain an integrated negative electrode for zinc-air battery.

[0042] (4) Preparation of zinc-air battery: The integrated negative electrode of the zinc-air battery is cut into a size of 40 mm × 40 mm × 5 mm, and then prepared into a negative electrode by welding the electrode ears, and assembled with the purchased positive electrode into a battery for standby use, which is numbered 3#.

[0043] Example 4 The preparation method of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: First weigh cellulose and zinc powder in a mass ratio of 1:4, then add them into deionized water, and mix them thoroughly in a planetary ball mill for 4 h at a stirring temperature of ≤40 °C. After stirring, move the precursor powder to a vacuum high and low temperature oven for drying at -5 °C for 48 h, grind and sieve to obtain a composite zinc powder precursor with an average particle size of 5-10 μm.

[0044] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed in a hydrogen-argon mixed gas environment at 650°C for 5 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 5 μm.

[0045] (3) Preparation of negative electrode: First, cyclodextrin and urea were mixed evenly in a mass ratio of 1:1 to form a mixed solubilizer. The spherical composite zinc powder was mixed with 1% solubilizer. After ultrasonic treatment for 30 minutes, the mixed powder was pressed into a block negative electrode by molding at a temperature of ≤100°C and a pressure of 100 MPa to obtain an integrated negative electrode for a zinc-air battery.

[0046] (4) Preparation of zinc-air battery: The integrated negative electrode of the zinc-air battery is cut into a size of 40 mm × 40 mm × 5 mm, and then prepared into a negative electrode by welding the electrode ears, and assembled with the purchased positive electrode into a battery for standby use, which is numbered 4#.

[0047] Example 5 The preparation method of the zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: First, weigh lactose and zinc powder in a mass ratio of 1:10, then add them into deionized water, and mix them thoroughly in a planetary ball mill for 4 h at a stirring temperature of ≤40 °C. After stirring, move the precursor powder to a vacuum high and low temperature oven for drying at -5 °C for 48 h. Grind and sieve to obtain a composite zinc powder precursor with an average particle size of 8 μm.

[0048] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed in a hydrogen-argon mixed gas environment at 650°C for 3 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 7 μm.

[0049] (3) Preparation of negative electrode: First, cyclodextrin and nicotinamide were mixed evenly in a mass ratio of 1:3 to form a mixed solubilizer, and the spherical composite zinc powder was mixed with 5% solubilizer. After ultrasonic treatment for 30 minutes, the mixed powder was pressed into a block negative electrode by molding at a temperature of ≤100°C and a pressure of 100 MPa to obtain an integrated negative electrode for a zinc-air battery.

[0050] (4) Preparation of zinc-air battery: Cut the integrated negative electrode of the zinc-air battery into a size of 40 mm × 40 mm × 5 mm, and then prepare it into a negative electrode by welding the pole ears, and assemble it with the purchased positive electrode into a battery for standby use, which is numbered 5#.

[0051] Comparative Example 1 A preparation method of a zinc-air battery comprises the following steps: (1) Preparation of composite zinc powder precursor: First weigh glucose and zinc powder in a mass ratio of 1:6, then add them into deionized water, and mix them thoroughly in a planetary ball mill for 4 h at a stirring temperature of ≤40 °C. After stirring, move the precursor powder to a vacuum high and low temperature oven for drying at 0 °C for 30 h. Grind and sieve to obtain a composite zinc powder precursor with an average particle size of 5-10 μm.

[0052] (2) Preparation of composite zinc powder: The composite zinc powder precursor was pyrolyzed in a hydrogen-argon mixed gas environment at 650°C for 2 h, and the carbon source material evenly wrapped on the surface of the Zn powder was in situ pyrolyzed into a carbon layer to obtain a spherical composite zinc powder with an average particle size of 10 μm.

[0053] (3) Negative electrode preparation: The mixed powder was solidified into a block negative electrode by using a discharge plasma sintering method at a temperature of 360°C and a pressure of 500 MPa to obtain an integrated negative electrode for a zinc-air battery.

[0054] (4) Preparation of zinc-air battery: The integrated negative electrode of the zinc-air battery is cut into a size of 40 mm × 40 mm × 5 mm, and then prepared into a negative electrode by welding the electrode ears, and assembled with the purchased positive electrode into a battery for standby use, which is numbered 6#.

[0055] Comparative Example 2 A preparation method of a zinc-air battery comprises the following steps: Preparation of negative electrode: first mix cyclodextrin and urea in a mass ratio of 1:1 to form a mixed solubilizer, then mix zinc powder with 1% of the mixed solubilizer, and then mix them in ultrasound for 30 minutes, and then use discharge plasma sintering to solidify the composite zinc powder into a block negative electrode at a temperature of 360°C and a pressure of 500MPa. Finally, cut the block negative electrode into a size of 40mm×40mm×5mm according to the integrated negative electrode of the zinc-air battery, and then prepare it into a negative electrode by welding the pole ears, and assemble it with the purchased positive electrode into a battery for standby use, numbered 7#.

[0056] Comparative Example 3 A preparation method of a zinc-air battery comprises the following steps: The 2mm thick zinc plate was surface-polished, degreased with acetone, cleaned with deionized water, and dried at 60°C. The integrated negative electrode of the zinc-air battery was cut into a size of 40mm×40mm×5mm, and then prepared into a negative electrode by welding the pole ears. It was assembled with the purchased positive electrode into a battery for standby use, numbered 8#.

[0057] The 1#-8# batteries prepared in the above examples and comparative examples were subjected to ohmic impedance tests using an electrochemical workstation. The test used a two-electrode system, a frequency of 0.01Hz-2MHz, and a disturbance frequency of 5mV. The results are as follows: Figure 1 ,Depend on Figure 1 It can be seen that the zinc negative electrode of the present invention has a three-dimensional continuous carbon network structure, and the ohmic impedance and polarization impedance are both smaller than those of the negative electrode without a carbon layer, indicating that the three-dimensional continuous carbon network structure can be used as an electron transmission channel between zinc powders, avoiding the increase in resistance caused by point contact between zinc powders, improving the electrode conductivity, and facilitating the deep charge and discharge of the battery. It can be seen from Comparative Examples 2 and 3 that when both zinc powder and zinc plate are not wrapped in a carbon layer, the ohmic impedance and polarization impedance of zinc powder are smaller than those of zinc plate, indicating that zinc powder has a discharge advantage when used as a negative electrode.

[0058] The 1#-4# batteries and 6#-8# batteries prepared in the above examples and comparative examples were subjected to constant current charge and discharge tests using an Arbin charger and discharger. The test current density was 10 mA / cm 2 , the discharge cut-off voltage is 0.9V, the charge cut-off voltage is 2.1V, and the negative electrode discharge capacity results are as follows Figure 2 As shown by Figure 2 It can be seen that the composite zinc powder and the solubilizer of the present invention have a higher negative electrode discharge capacity and better performance when used in combination than when used alone. By comparing the gram capacities of Comparative Examples 1-3, it is found that the addition of a single composite zinc powder and a single solubilizer results in the two negative electrode gram capacities being much higher than that of the zinc plate, indicating that the composite zinc powder and the solubilizer have the effect of improving the negative electrode discharge performance.

[0059] The 1#-4# batteries and 6#-8# batteries prepared in the above examples and comparative examples were subjected to LSV performance tests using an electrochemical workstation. The test voltage range was scanned from the open circuit voltage to 0.1V, and the scan amplitude was 0.05V / s. The results are as follows: Figure 3 As shown by Figure 3 It can be seen that the performance of the zinc negative electrode prepared by different metal consolidation methods used in the present invention is different, among which the negative electrode prepared by the spark plasma sintering method has the best performance, followed by the compression molding method. Through the examples and comparative examples, it is found that the maximum power density of the zinc powder negative electrode is much greater than that of the zinc plate, and the maximum power density is greater when the composite zinc powder and the solubilizer are mixed than when they are used alone, and the negative electrode performance is better.

Claims

1. A method for preparing an integrated negative electrode for a zinc-air battery, characterized in that: The following steps are involved: (1) Preparation of composite zinc powder precursor: adding carbon source material and zinc powder into solvent, mixing by ball milling, drying under vacuum conditions, grinding and sieving to obtain composite zinc powder precursor; (2) Preparation of composite zinc powder: The composite zinc powder precursor is pyrolyzed in situ in a hydrogen-argon mixed gas environment to obtain composite zinc powder; (3) Negative electrode preparation: The composite zinc powder is mixed with a solubilizer, and after ultrasonic treatment, a block negative electrode is prepared by a metal consolidation method to obtain an integrated negative electrode for a zinc-air battery.

2. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The mass ratio of the carbon source material to the zinc powder in step (1) is 1:1-15.

3. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The carbon source material in step (1) is one of glucose, sucrose, lactose, starch and cellulose.

4. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The ball milling mixing time of step (1) is 2-8 hours, the drying temperature under vacuum conditions is -10-5°C, the drying time under vacuum conditions is 24-48 hours, and the average particle size after grinding and sieving is 5-10 μm.

5. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The temperature of the in-situ pyrolysis in step (2) is 650-850°C, and the time of the in-situ pyrolysis is 2-7h.

6. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The solubilizer in step (3) is one or more of cyclodextrin, nano calcium oxide particles, potassium acetate, urea, acetamide, and nicotinamide, and the particle size of the solubilizer is ≤50 nm.

7. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The amount of the solubilizing agent used in step (3) is 0.1-5% of the mass of the spherical composite zinc powder.

8. The method for preparing the integrated negative electrode of a zinc-air battery according to claim 1, characterized in that: The metal consolidation method in step (3) is one of spark plasma sintering, 3D printing, cold pressing and compression molding.

9. A zinc-air battery integrated negative electrode, characterized in that: The zinc-air battery integrated negative electrode is prepared by the preparation method of the zinc-air battery integrated negative electrode according to any one of claims 1 to 8.

10. An application of the integrated negative electrode of a zinc-air battery according to claim 9, characterized in that: The prepared zinc-air battery integrated negative electrode is made into a negative electrode according to the size and shape, and then assembled into an air battery with an air positive electrode and an alkaline electrolyte.

Citation Information

Patent Citations

  • Preparation method of alkaline cell cathode rod

    CN101252182A

  • Aqueous zinc ion battery and preparation method and application thereof

    CN110867579A

  • Bismuth trioxide modified indium-doped zinc oxide material and preparation and application thereof

    CN114551873A

  • Three-dimensional carbon skeleton zinc composite material for negative electrode of dendrite-free zinc metal battery and preparation method of three-dimensional carbon skeleton zinc composite material

    CN115986099A

  • Three-dimensional zinc-philic current collector composite negative electrode constructed in electrochemical welding mode

    CN116404097A